Apparebit repentina dies: Hindemith’s musical panorama of Judgment Day - Bruhn, Siglind (Interdisciplinary Studies in Musicology, 2014)
In 1947, while teaching at Yale University, the German composer Paul Hindemith (1895-1963) wrote a composition for mixed chorus and brass ensemble based on an anonymous Latin hymn believed to date from the 8th century or before. This text, which he had discovered in The Oxford Book of Medieval Latin Verse, tells in a poetic rewording of New T estament passages of the events to be expected on Judgment Day. Below a deceptively simple surface with regular trochaic tetrameters organized in 23 couplets that are launched by the consecutive letters of the alphabet, the hymn hides various dramatic perspectives. These include a narrator announcing what is to come and later describing what he witnesses in a vision, direct-speech dialogues between Christ as the Judge of the World and the two groups of the chosen and the damned, and a concluding moral admonishment addressed by the pious author to his contemporary listeners or latter-day readers. As the analysis of the musical structure and texture, meter and rhythm, thematic material and tonal organization shows, Hindemith achieves a semiotic rendering of these aspects and many finer nuances. Just as the medieval text ostensibly uses only one mode throughout without depriving the message of any of its colorful expressiveness, so Hindemith’s music uses only one constellation of sound colors — choral singing against or in alternation with ten brass instruments — to bring the multifaceted scene to life. This music is both text setting and scenic painting, replete with refined allusions as well as onomatopoeic depiction, weaving a web of signification with which the composer at once heightens and deepens the early poet’s message.